2019
DOI: 10.1055/s-0039-1681094
|View full text |Cite
|
Sign up to set email alerts
|

Are Joint Surgeons Being Adequately Compensated for Single-Component versus Double-Component Revision TKA? An Analysis of Relative Value Units

Abstract: Relative value units (RVUs) are used for ensuring that physicians are appropriately reimbursed based on case complexity. While past research has elucidated that surgeons are reimbursed at a higher rate for primary total knee arthroplasty (TKA) versus revision TKA, no study has explored differences in reimbursements between single-component and double-component revisions, considering a double-component revision is likely to require more effort/skill as compared with single-component revision. The 2015 to 2016 A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 8 publications
1
11
0
Order By: Relevance
“…However, it is unclear whether reimbursement algorithms consider the higher resource utilization, complexity, and operative time associated with the burden of infection management with rTHA-I. Although multiple studies exploring revision total knee arthroplasties have demonstrated inadequate compensation for those due to infection [41][42][43][44] , there remains minimal information regarding whether this disparity is found for rTHA procedures. Our analysis demonstrated a consistent devaluation of both types of rTHA procedures over the past 18 years.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is unclear whether reimbursement algorithms consider the higher resource utilization, complexity, and operative time associated with the burden of infection management with rTHA-I. Although multiple studies exploring revision total knee arthroplasties have demonstrated inadequate compensation for those due to infection [41][42][43][44] , there remains minimal information regarding whether this disparity is found for rTHA procedures. Our analysis demonstrated a consistent devaluation of both types of rTHA procedures over the past 18 years.…”
Section: Discussionmentioning
confidence: 99%
“…In a similar analysis looking at total knee arthroplasties (TKAs), the authors found that revision TKAs were being under-valued with a physician reimbursement rate of $7.90/min compared with $9.33/min for primary TKAs. 7 Malik et al 8 analyzed over 6,000 cases of single- and double-component revision TKAs, and de-lineated that despite the longer surgical times and greater effort required for doing a double-component revision TKA providers are reimbursed at lower rate of $8.00/min compared with $9.58/min for a single-component revision TKA.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8] Prior studies in the orthopedic literature have compared reimbursement for specific Current Procedural Terminology (CPT) codes and found that typically longer and more complex procedures are not appropriately compensated when compared to shorter ones. [9][10][11][12][13][14] Understanding reimbursement patterns is the first step in identifying any mismatches between reimbursement and work performed for categories of procedures to help direct policy changes by subspecialty organizations. Understanding these patterns also better enables orthopedists to advocate for fair compensation for a given procedure.…”
Section: Introductionmentioning
confidence: 99%
“… 5 , 6 , 7 , 8 Prior studies in the orthopedic literature have compared reimbursement for specific Current Procedural Terminology (CPT) codes and found that typically longer and more complex procedures are not appropriately compensated when compared to shorter ones. 9 , 10 , 11 , 12 , 13 , 14 …”
Section: Introductionmentioning
confidence: 99%